Griffin's Castle - Nimmo, Jenny (Orchard Books, 1997)
After years of having moved around, eleven-year-old Dinah determines to make a huge, dilapidated old mansion into a home for her mother and herself, but the wild beasts she summons from a stone wall to protect her may also imprison her.